Role of Finite State Automata in Transliterating Latin Script into Javanese Script - Suprihatin, Suprihatin; Riadi, Imam; Furizal, Furizal; D.E Purwadi Putra, Izzan Julda (Department of Informatics, Universitas Muhammadiyah Surakarta, Indonesia, 2023)
Writing Javanese script is considered complicated and difficult for people who learn it. The process of transliterating Latin into Javanese script cannot be done directly, because each alphabet is not always represented by one Javanese script. Javanese script is not represented by one or more Latin letters, so if transliteration of Latin letters to Javanese letters is required, a parsing process is required. The rows of Javanese letters form a ligature with certain rules, so parsing is also needed to arrange the rows of Javanese letters correctly. This study aims to design a program to facilitate the transliteration of Latin script to Javanese script. Finite State Automata (FSA) is used to describe writing rules. This study is limited to lowercase letters only, capital letters will be subtracted first, number symbols are not discussed in this study. The results of the study are in the form of a program design that can transliterate Latin writing into Javanese. Experiments were carried out as many as 4 structures of vowel consonant variations. All syllabic structures that include KV, KKV, KVK, KKVK have been tried. The transliteration results show conformity with a 100% accuracy rate in accordance with the rules of writing Javanese script. This research shows that the application of FSA can handle the transliteration of Latin letters into Javanese.